Dust cleaning device based on Ultrasonic sensors using Arduino Mega - Pratama Anamendra, Firzan; Candra, Oriza (Journal of Industrial Automation and Electrical Engineering, 2025)
This study develops an automatic vacuum cleaner based on ultrasonic sensors with Arduino Mega as the main control unit. This system is designed to improve cleaning efficiency with automatic navigation that can detect and avoid obstacles without requiring a line path as a guide. This tool can move automatically using ultrasonic sensors to detect obstacles around it and adjust its direction of movement so as not to hit objects blocking its path. This tool integrates an HC-SR04 ultrasonic sensor, DC motor, L298N motor driver, and a relay to control the vacuum cleaner. Testing was carried out on an area of ​​120 cm × 120 cm divided into nine boxes, with an average cleaning result of 8.4 papers/box. These results indicate that the tool has effective and reliable cleaning capabilities. With this innovation, automatic vacuum cleaners can provide a practical solution for people in maintaining home cleanliness efficiently.